Exploring and Mitigating Privacy Threats of HTML5 Geolocation API - Kim, Hyungsub; Lee, Sangho; Kim, Jong (30th Annual Computer Security Applications Conference (ACSAC 2014), 2014)
The HTML5 Geolocation API realizes location-based services via the Web by granting web sites the geographical location information of user devices. However, the Geolocation API can violate a user’s location privacy due to its coarse-grained permission and location models. The API provides either exact location or nothing to web sites even when they only require approximate location. In this paper, we ﬁrst conduct case studies on numerous web browsers and web sites to explore how they implement and utilize the Geolocation API. We detect 14 vulnerable web browsers and 603 overprivileged web sites that can violate a user’s location privacy. To mitigate the privacy threats of the Geolocation API, we propose a novel scheme that (1) supports ﬁne-grained permission and location models, and (2) recommends appropriate privacy settings to each user by inspecting the location sensitivity of each web page. Our scheme can accurately estimate each web page’s necessary geolocation degree (estimation accuracy: ∼93.5%). We further provide suggestions to improve the Geolocation API.